Atherogenic Index of Plasma in Postmenopausal Women - Khakurel, Gita; Kayastha, Rajat; Chalise, Sanat; Karki, Prabin K (Journal of Nepal Health Research Council, 2018)
Background: Hyperlipidemia is one of the important risk factor for development of cardiovascular disease  in post menopausal women.Our study compared the serum lipid profile and atherogenic index of plasma  between premenopausal and  post menopausal women.Methods: This was a cross sectional study conducted in Kathmandu Medical College.  A total number of 194 women in the age group 30 to 60 years were studied. They include 108 postmenopausal women and 86 premenopausal controls. Total cholesterol, low density lipoprotein cholesterol, high density lipoprotein cholesterol  and triglycerides  were determined. Results: The mean value of total cholesterol, low-density lipoprotein cholesterol and triglyceride were significantly increased in postmenopausal women when compared to premenopausal women. There was increase in high-density lipoprotein cholesterol  in postmenopausal women but the difference was not significant. The atherogenic index of plasma was  increased in postmenopausal women (0.22 ± 0.25 mmol/l). This shows that postmenopausal women in our setting are at medium risk of developing cardiovascular disease. Atherogenic index of plasma was positively and significantly correlated with age (r= 0.29, p